Silicon Disruption: An Event Study of DeepSeek R1’s Breakthrough Impact on Semiconductor Markets - Han Zongshuo (SHS Web of Conferences, 2025)
This paper conducts an event study to examine the US stock market response to the launch of the DeepSeek R1 model by its Chinese competitor, as well as to assess how US semiconductor manufacturers reacted to this launch. Which is a little new AI-large language model, designed to challenge the performance level of the existing AIs, such as Hudy, Claude-3 and o1-mini. 5. The results from the event study show a significant negative reaction from investors to US semiconductor stocks in response to the release of the DeepSeek R1 model. Furthermore, the effect is stronger among specialized AI service companies than larger core AI service companies. Hence, this article gives new insights into how the stock market responded to the DeepSeek R1 when it first was introduced. This issue discusses strong empirical evidence on the impact of a unique AI technology launch on investor sentiment in the US semiconductor industry; it also provides policy makers and industry leaders with deep insights into possible paths for winning in global technocompetition.